Determinan Eksploitasi Pekerja Anak Sektor Informal dari Sisi Jam Kerja di Indonesia Tahun 2021 - Wahyuni Wahyuni; Liza Kurnia Sari (Seminar Nasional Official Statistics, 2022)
Children have the right to receive protection and fulfillment of physical and spiritual needs, but some children are forced to work, which makes children vulnerable to exploitation. The percentage of child laborers who are exploited by working hours has continued to increase from 2018 to 2020. The informal sector is the most chosen sector by child labor, but the informal sector does not have contracts and social protection to increase the opportunities for child labor to be exploited. This study aims to determine the general description, the variables that influence, and the tendency to exploit child labor in the informal sector by working hours in Indonesia. Susenas 2021 data were analyzed using binary logistic regression. The region classification, age of head of household, education of the head of household, and gender of children significantly affect child labor exploitation in the informal sector by working hours.